Leadership Ethos and Trust Deficits in Indonesian Education: An Analytical Case Study - Darmawan, Wahyu; Mank, Minhajul Abidin (Development: Studies in Educational Management and Leadership, 2024)
This paper critically assesses the implementation of educational policies at Madrasah Darul Amin and emphasizes that effective leadership is key to improving the quality of education. Through qualitative case studies, data was obtained from observations, in-depth interviews, and document analysis. The findings show that education policy is not merely oriented towards compliance, but is shaped by the diverse needs of students and the demands of the national curriculum to create a relevant and quality learning experience. The principal acts as a facilitator of change by encouraging innovative teaching methods and the integration of educational technology to increase student engagement. A collaborative culture among teachers—supported by open communication and teamwork—emerged as an important prerequisite for successful implementation. Teacher participation in decision-making strengthened their sense of ownership and commitment to the policy, emphasizing the urgency of democratic leadership. In addition, regular monitoring and evaluation are necessary to make continuous adjustments to optimize policy effectiveness. This study concludes that proactive and collaborative leadership, accompanied by active teacher involvement, significantly improves the quality of education at Madrasah Darul Amin. To maintain and expand these achievements, it is recommended to strengthen communication with stakeholders, encourage pedagogical innovation, strengthen collaboration, and implement continuous evaluation.